The phenomenon of consciousness flow in Ukrainian literature and its psychoanalytic reconstruction - Kuznetsov, Yuriy (Psyhology & society, 2019)
The methodological study is devoted to illuminating the forms, methods and means of cognitive reconstruction of the consciousness flow of literary heroes in the works of the “new generation” writers (Ivan Franko). We are talking about the artistic talent of Mykhailo Kotsubynskiy (1864–1913) and a number of his famous works (“Apple Blossom”, “Intermezzo”, “Pupa”), imbued with sophisticated psychology, a special existence of the heroes’ internal experiences in the actualizing transformations of several flows of their awareness – consciousness, subconsciousness, the superconsciousness. It is shown for the first time that in depicting the everyday life of heroes, it was this prominent Ukrainian writer who reached a level of deep psychological cognition, which was not the case in the literature of the 19th century. In particular, performing mental-aesthetic quality of the works, he was able to depict the entire structural and dynamic palette of the psychic life, which by that time science was characterized as a topic of the human’s mental world. The result of the research revealed many similarities between M. Kotsubynskyi’s artistic work and the scientific-natural cognition of S. Freud, who positively correlated with each other, although they didn’t know each other and weren’t familiar with each other’s works. If S. Freud treated mental disorders and injuries of the subconsciousness by the method of free associations, while decoding the latent effect of mental mechanisms (displacement, projection, replacement, rationalization, etc.), then M. Kotsubynskyi had depicted the course of the subconsciousness mental processes by artistic techniques, primarily such as subtext, repeat, metaphor, prospecting and retrospection. Therefore, it is natural that the works of Mykhailo Kotsubynskyi are at the top not only for Ukrainian, but also for world literature. No one was able to transform the work-landscape into a “language” of the human soul with its crisis and dramatic states. A psychoanalytic interpretation makes it possible to translate the symbols of flowers, nature into the language of mental storms, traumas and recovery. In addition, a new concept has been introduced into scientific circulation – “artistic psychoanalysis”, in analogy to the already existing – “artistic psychology”. The last one signifies the phenomenon when the writer depicts the deep processes in the hero’s soul, down to the subconsciousness. It is proved that Ukrainian writers of the “new generation”, as well as European artists, reached exactly such depths. In particular, Kotsubynskyi made artistic discoveries that were partly ahead of S. Freud’s bold hypotheses.